2002
DOI: 10.2298/hel0237059t
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and phosphorus levels and ratios on seed yield and nutrient uptake of sunflower hybrid DSH-I

Abstract: A field experiment was conducted on medium black clayey soils under rainfed conditions at Main Research Station, University of Agricultural Sciences (UAS), Dharwad, India, during kharif 1999 to study the effect of different levels and ratios of nitrogen and phosphorus on seed yield and nutrient uptake of the sunflower hybrid DSH-1. The experiment consisted of nine treatments, i.e., N/P ratios with two N/P ratios of <1.0 (0.67 and 0.80), N/P ratio of 1.0 consisting of two ratios and four N/P ratios of >1.0 (1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 1 publication
5
12
0
1
Order By: Relevance
“…This increase could also be attributed to the positive effect of farm yard manure along with NPK in increasing the nutrients uptake leading to higher dry matter production. Similar results have been reported by Ram et al (1992) in sunflower, Shivaprasad et al (1996) in sunflower Sarmah et al (2000) in sunflower, Thavaprakash (2000) in sunflower and Anand (2010) in sunflower and maize. Application of SSNM for 1.2 t ha -1 + FYM (T 9 ) recorded significantly (P=0.05) more number days to 50 per cent flowering (64.88 days) and days to maturity (104.75 days) compared to T 1 (RDF + FYM) (62.62 and 101.35 days to 50 per cent flowering and maturity respectively).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This increase could also be attributed to the positive effect of farm yard manure along with NPK in increasing the nutrients uptake leading to higher dry matter production. Similar results have been reported by Ram et al (1992) in sunflower, Shivaprasad et al (1996) in sunflower Sarmah et al (2000) in sunflower, Thavaprakash (2000) in sunflower and Anand (2010) in sunflower and maize. Application of SSNM for 1.2 t ha -1 + FYM (T 9 ) recorded significantly (P=0.05) more number days to 50 per cent flowering (64.88 days) and days to maturity (104.75 days) compared to T 1 (RDF + FYM) (62.62 and 101.35 days to 50 per cent flowering and maturity respectively).…”
Section: Resultssupporting
confidence: 86%
“…Thus, under assured nutrition environment extending the vegetative phase by putting better growth and delaying flowering as well as translocation of assimilates to sink by delaying maturity. Similar results have been reported by Tripathiand Kalra (1981) in sunflower, Tomar et al (1997) in sunflower, Thavaprakash (2000) in sunflower, Singh et al (2016) in rice, Singh et al (2017) in rice and wheat and Basavanneppa et al (2016) in Bt cotton. Yield components of sunflower: In the present study, application of SSNM for target yield of 1.2 t ha -1 + FYM (T 9 ) produced significantly (P=0.05) higher hybrid seed yield (1003 kg ha -1 ) and stalk yield (1883 kg ha -1 ) over recommended package (T 1 :RDF+ FYM) which gave significantly lower seed yield (797 kg ha -1 ) and stalk yield (1714kg ha -1 ).…”
Section: Resultssupporting
confidence: 84%
“…Sunflower hybrids have significant effect on AY. Hybrid S-278 had higher achene oil yield (1405 and 1423 kg ha -1 ) than Hysun-33 (1191 and 1209 kg ha -1 ) in 2010 and 2011, respectively, which might be due to genetic characteristics of sunflower hybrids as explained by Flagella et al (2002), Vega and Hall (2002), Thavaprakash et al (2002), Zheljazkov et al (2008), (2009), and Arshad et al (2009), who also reported similar results regarding achene oil yield.…”
Section: Achene and Oil Yieldmentioning
confidence: 58%
“…With regard to average years, oil content of medium-early C-70165 cultivar (43.4 %) was higher than the oil content of early Isera (40.3 %) and late Teknosol cultivar (34.1 %). In previous studies, oil content of sunflower cultivars was reported as 41.46% by Thavaprakash (2004), as 41.3% by Tuncturk et al (2005), as between 39.1-45.9% by Karaaslan et al (2007) and as between 38.0-53.4% by Kaya et al (2009). Current findings comply with the results of those earlier studies.…”
Section: Oil Contentmentioning
confidence: 90%
“…Thusly in previous studies, Ozer et al (2004) reported significant effects of nitrogenous fertilizers on seed yield and quality and Ali et al (2012) and Nasim et al (2012) reported increasing sunflower yield levels with increasing nitrogen doses. Thavaprakash (2004) and Namvar et al (2012) observed the highest seed yield levels at 12 kg nitrogen dose and Evci et al (2006) reported the highest yield at nitrogen doses of between 5-10 kg. Current findings also comply with the results of those previous studies.…”
Section: Seed Yieldmentioning
confidence: 96%